THE EFFECT OF BRAIN-BASED LEARNING APPROACH ON CRITICAL THINKING ABILITY AND LEARNING MOTIVATION OF ELEMENTARY SCHOOL STUDENTS IN SCIENCE SUBJECTS - Muhamad Dawam Raihan; Asep Supena; M. Syarif Sumantri; Gumgum Gumelar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT This study aims to determine the impact of the Brain-Based Learning (BBL) approach on critical thinking skills and learning motivation of primary school students in science subjects. This study used a quasi-experimental design with pretest-posttest. The sample of this study consisted of two fifth-grade classes selected by a simple random sampling technique. The population of this study was all fifth-grade students in an elementary school in the Cinangka sub-district, Serang Regency. Data were obtained through test and non-test techniques. The results showed that the BBL approach affected students' critical thinking skills (sig. 2-tailed = 0.002 < α = 0.05). In addition, it also improved students' critical thinking skills as represented by the N-Gain value (experimental class N-Gain = 0.45 > control class N-Gain = 0.22). On the other hand, the BBL approach not only has a significant effect on students' critical thinking skills but also on students' science learning motivation (sig. 2-tailed = 0.000 < α = 0.05) and can increase it (experimental class N-Gain = 0.58 > control class N-Gain = 0.05). This means that the BBL approach can improve students' critical thinking skills and learning motivation more effectively than the traditional approach. Keywords: Brain-based Learning; Critical Thinking Ability; Science Learning Motivation. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh pendekatan Brain-Based Learning (BBL) terhadap kemampuan berpikir kritis dan motivasi belajar siswa sekolah dasar pada mata pelajaran IPA. Penelitian ini menggunakan desain kuasi eksperimen dengan pretest-posttest. Sampel penelitian ini terdiri dari dua kelas kelas lima yang dipilih dengan teknik simple random sampling. Populasi penelitian ini adalah seluruh siswa kelas lima di sebuah sekolah dasar di Kecamatan Cinangka Kabupaten Serang. Data diperoleh melalui teknik tes dan nontes. Hasil penelitian menunjukkan bahwa pendekatan BBL berpengaruh terhadap kemampuan berpikir kritis siswa (sig. 2-tailed = 0,002 < α = 0,05). Selain itu, pendekatan BBL juga meningkatkan kemampuan berpikir kritis siswa yang ditunjukkan dengan nilai N-Gain (N-Gain kelas eksperimen = 0,45 > N-Gain kelas kontrol = 0,22). Di sisi lain, pendekatan BBL tidak hanya berpengaruh signifikan terhadap kemampuan berpikir kritis siswa tetapi juga terhadap motivasi belajar IPA siswa (sig. 2-tailed = 0,000 < α = 0,05) dan dapat meningkatkannya (N-Gain kelas eksperimen = 0,58 > N-Gain kelas kontrol = 0,05). Hal ini berarti bahwa pendekatan BBL dapat meningkatkan kemampuan berpikir kritis dan motivasi belajar siswa lebih efektif dibandingkan dengan pendekatan tradisional. Kata Kunci: Pembelajaran Berbasis Otak; Kemampuan Berpikir Kritis; Motivasi Belajar IPA.